Analisis Bidang Permasalahan Belajar Siswa Berdasarkan Hasil AUM PTSDL pada Kelas IX-2 di UPT SMP Negeri 11 Medan - Annisa Ayuni Zahra; Epenta Sitepu; Riffa Hafidzah Hendri; Zahara Salsabila (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Students’ learning difficulties are often not specifically identified, resulting in guidance and counseling services that do not fully meet their needs. This situation indicates a gap between students’ actual needs and the data used as the basis for service planning. This study aims to analyze the areas of students' learning problems based on the results of the PTSDL Problem Identification Tool (AUM) in class IX-2 at UPT SMP Negeri 11 Medan. This study uses a quantitative descriptive method with data collection techniques through the distribution of the PTSDL AUM instrument to 23 students. Data were analyzed through scoring and percentage calculations across five aspects: prerequisites for mastering the material, learning skills, learning resources, personal conditions, and the socio-emotional environment. The results of the study indicate that the dominant issue lies in the aspect of learning skills (27.13%), followed by personal conditions (11.75%) and the socio-emotional environment (6.85%), while learning resources (4.2%) and prerequisites for mastering the material were relatively low. These findings indicate that students’ primary difficulties lie in managing the learning process. In conclusion, guidance and counseling services need to focus on developing learning skills and strengthening students’ personal conditions to optimize learning.